THE EFFECT OF PRODUCT QUALITY, PRODUCT DESIGN AND PRICE ON THE PURCHASING DECISION OF YAMAHA FILANO MOTORCYCLES IN THE LHOKSEUMAWE CITY COMMUNITY - T. Edyansyah; Rico Nur Ilham; Muhammad Roni (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to determine the effect of product quality, product design, and price on purchasing decision for Yamaha Filano motorcycles among the people of Lhokseumawe City. The independent variables in this study are product quality, product design, and price, while the dependent variable is purchasing decisions. The data used are primary data obtained through distributing questionnaires to 137 respondents who have purchased Yamaha Filano motorcycles. The sampling technique used is incidental sampling. The data analysis method used is multiple linear regression. The results of the study indicate that partially product quality, product design, and price have a positive and significant effect on purchasing decisions for Yamaha Filano motorcycles. Simultaneously, the three independent variables also have a significant effect on purchasing decisions. This study is expected to be a consideration for companies in improving product quality, paying attention to product design, and setting prices that are in accordance with consumer needs and abilities.